Synthesis, Characterization And Microbial Activity Of New Thiazole, Thiazolidinone, Thiadiazole And Phenylacrylohydrazide Substituted Coumarin Derivatives - Yusuf Zai, Samina Khan (2015)

(untitled)
Thiazol, thiazolidinon, thiadiazol, fenilakrilohidrazid dan kumarin merupakan sebahagian daripada kelas sebatian heterosiklik yang mempunyai kepentingan dalam bidang perubatan dan farmakologi. Dalam kajian ini enam siri daripada 67 sebatian kumarin baru yang aktif secara biologi telah disintesis dengan mencantumkan unit thiazol, thiazolidinon, thiadiazol dan fenilakrilohidrazid ke dalam rangka kumarin untuk meningkatkan kegunaannya sebagai agen terapeutik yang penting. Semua terbitan yang telah disintesis dicirikan menggunakan teknik spektroskopik seperti IR, 1D NMR (1H dan 13C) dan analisis CHN bersama LC-MS. Struktur terbitan terpilih telah dipastikan lebih dengan lanjut menggunakan teknik spektroskopik 2D NMR (COSY, HMQC dan HMBC). Di samping itu, analisis pembelauan X-Ray telah digunakan bagi mengesahkan struktur sebatian yang diperolehi adalah kristal tunggal. Struktur semua bahan permulaan yang disintesis telah disahkan dengan membandingkan data spektroskopi tersebut dengan yang telah dilaporkan dalam literatur. Sukatan takat lebur telah dijalankan kepada semua sebatian bagi memeriksa ketulenan mereka. Thiazoles, thiazolidinones, thiadiazoles, phenylacrylohydrazides and coumarins, are few of the very important classes of heterocyclic compounds having great medicinal and pharmacological importance. In the present study, six series of 67 new biologically active coumarin derived compounds have been synthesized by substituting thiazole, thiazolidinone, thiadiazole and phenylacrylohydrazide units into the coumarin core, in order to increase their use as important therapeutic agents. The structures of all the new compounds were characterized by spectroscopic techniques such as, IR, 1D NMR (1H and 13C) and CHN analysis together with LCMS. The structures of the selective compounds from each series were further confirmed by 2D NMR (COSY, HMQC and HMBC) spectroscopic techniques. In addition to this X-Ray diffraction analysis was used to confirm, the structures for those compounds obtained as single crystals. The structures of all the synthesized starting materials were confirmed by the comparison of their spectroscopic data with those already reported in literature. Melting point measurements was done for all the synthesized compounds, in order to check their purity.